Observations on the biological traits of the rare shark Oxynotus centrina (Chondrichthyes: Oxynotidae) in the Hellenic Seas - V. Kousteni; P. Megalofonou (Journal of Fish Biology, 2016)
New records of the rare angular rough shark Oxynotus centrina from the Hellenic Seas are presented. Its occurrence is reported for the first time in the Corinthian Gulf. Some aspects of the species' biology are described and compared with previous studies.

Evidence of high genetic connectivity for the longnose spurdog Squalus blainville in the Mediterranean Sea - V. KOUSTENI; P. KASAPIDIS; G. KOTOULAS; P. MEGALOFONOU (Mediterranean Marine Science, 2015)
Squalus blainville is one of the least studied Mediterranean shark species. Despite being intensively fished in several locations, biological knowledge is limited and no genetic structure information is available. This is the first study to examine the genetic structure of S. blainville in the Mediterranean Sea. Considering the high dispersal potential inferred for other squalid sharks, the hypothesis of panmixia was tested based on a 585 bp fragment of the mitochondrial DNA cytochrome c oxidase subunit I gene from 107 individuals and six nuclear microsatellite loci from 577 individuals. Samples were collected across the Ionian, Aegean and Libyan Seas and off the Balearic Islands. Twenty three additional sequences of Mediterranean and South African origin were retrieved from GenBank and included in the mitochondrial DNA analysis. The overall haplotype diversity was high, in contrast to the low nucleotide diversity. Low and non-significant pairwise ΦST and FST values along with a Bayesian cluster analysis suggested high connectivity with subsequent genetic homogeneity among the populations studied, and thus a high dispersal potential for S. blainville similar to other squalids. The historical demography of the species was also assessed, revealing a pattern of population expansion since the middle Pleistocene. These findings could be considered in species-specific conservation plans, although sampling over a larger spatial scale and more genetic markers are required to fully elucidate the genetic structure and dispersal potential of S. blainville.

Age estimation of juvenile European hake Merluccius merluccius based on otolith microstructure analysis: a slow or fast growth pattern? - P. Pattoura; E. Lefkaditou; P. Megalofonou (Journal of Fish Biology, 2015)
The main goal of this study was to examine otolith microstructure and to estimate the age and growth of European hake Merluccius merluccius from the eastern Mediterranean Sea. One hundred and twenty‐nine specimens ranging from 102 to 438 mm in total length ( L T ) were used. Age estimations were based on the study of the otolith microstructure, which was revealed after grinding both frontal sides of otoliths. The enumerations of the daily growth increments ( DGI ) as well as their width ( W DGI ) measurements were made on calibrated digital images. The number of DGI in otoliths ranged between 163 and 717. Four phases in the W DGI evolution were distinguished: (1) larval–juvenile pelagic phase, with an increasing trend in W DGI up to the 60th DGI, (2) settlement phase, with a short‐term deceleration in W DGI between the 61st and 150th DGI, (3) juvenile demersal phase, characterized by a stabilization of W DGI from 151st to 400th DGI and (4) adult phase, with a decreasing trend in W DGI after the 400th DGI. Age, sex and month of formation were found to affect the W DGI in all phases, with the exception of age at the juvenile demersal phase. The power curve with intercept model described best the relationship of M. merluccius L T with age ( T DGI ), according to Akaike criteria, revealing differences in growth between females [ L T = 65 · 36( T DGI ) 0 · 40 − 388 · 55] and males [ L T = 69 · 32( T DGI ) 0 · 37 − 352 · 88] for the sizes examined. The mean daily growth rates were 0·61 mm day −1 for females and 0·52 mm day −1 for males, resulting in an L T of 283 and 265 mm at the end of their first year of life. In comparison with previous studies on the Mediterranean Sea, the results of this study showed a greater growth rate, similar to results from tagging experiments and otolith microstructure analyses for M. merluccius in other geographic areas.

New Mediterranean Biodiversity Records (June 2012) - A. NICOLAIDOU; G. ALONGI; O. AYDOGAN; M. CATRA; L. CAVAS; C. CEVIK; A. DOSI; V. CIRCOSTA; S. GIAKOUMI; F. GIMENEZ-CASALDUERO; H. FILIZ; A. IZQUIERDO-MUNOZ; et al. (Mediterranean Marine Science, 2012)
The present work reports on the extended distribution of nineteen species in the Mediterranean. These are: Upeneus pori(Fish:Turkey), Bursatella leachii (Mollusca, Opisthobranchia: eastern coast of Spain), Sparisoma cretense (Fish: Ionian coastof Greece), Pseudobryopsis myura (Chlorophyta: Turkey), Aplysia dactylomela (Mollusca, Opisthobranchia: Karpathos island,and Kyklades Archipelago, Greece), Asparagopsis armata and Botryocladia madagascariensis (Rhodophyta: South Peloponnesos,Greece), Oxynotus centrina (Fish: Greece), Caulerpa racemosa var. cylindracea (Chlorophyta ), Stypopodium schimperi(Phaeophyta ) Siganus luridus and Stephanolepis diaspros (Fish) Percnon gibbesi (Decapoda, Brachyura) (Kyklades Archipelago,Greece), Cerithium scabridum (Mollusca, Prosobranchia: Anavissos: Greece) and Cerithium renovatum (Mollusca, Prosobranchia:N. Κriti), Cassiopea andromeda (Scyphomedusa: Rhodos Island, Greece), Abra tenuis (Mollusca Bivalvia: VouliagmeniLake, Greece) Lagocephalus lagocephalus (Fish: Calabrian coast, Italy) and Plocamopherus ocellatus (Mollusca, Opisthobranchia:İskenderun Bay, Turkey).

Germ cell proliferation and apoptosis during different phases of swordfish ( Xiphias gladius L.) spermatogenetic cycle - A. Corriero; S. Desantis; C. R. Bridges; D. E. Kime; P. Megalofonou; N. Santamaria; F. Cirillo; G. Ventriglia; A. Di Summa; M. Deflorio; F. Campobasso; G. De Metrio (Journal of Fish Biology, 2007)
Seasonal changes of testicular activity of the swordfish Xiphias gladius and correlations of plasma levels of testosterone (T) and 11‐ketotestosterone (11‐KT) with proliferation and apoptosis of germ cells, determined, respectively, with monoclonal antibodies against proliferating cell nuclear antigen and terminal deoxynucleotidyl transferase‐mediated d’UTP nick end labelling, are described. Three phases of the reproductive cycle were found: active spermatogenic (May), spawning (June to July) and spent (August to September) stages. Germ cell proliferating activity was highest in May, decreased during June to July and remained stable during August to September. Apoptotic germ cells, primary spermatocytes and spermatogonia, were present in all the specimens analysed and were more abundant in May. The levels of 11‐KT in plasma were always higher than T and were highest in May, in concomitance with the maximum proliferation and apoptosis rate of germ cells.

Biochemical composition of the Atlantic bonito Sarda sarda from the Aegean Sea (eastern Mediterranean Sea) in different stages of sexual maturity - N. Zaboukas; H. Miliou; P. Megalofonou; M. Moraitou‐Apostolopoulou (Journal of Fish Biology, 2006)
The content (% wet mass) in water, ash, lipid, crude protein, DNA and RNA of different tissues was determined during sexual maturation of bonitos Sarda sarda from the Aegean Sea. A total of 220 specimens were collected in the following stages of sexual maturity: immature, resting, developing, mature, spawning and spent. Highest lipid levels in the white muscle, red muscle and liver were measured in immature specimens, while lowest levels were found in spawning bonitos. The gradual percentage of lipid reduction from immature to spawning bonitos was relatively higher in the liver (females 71·2% and males 64·4%) than in the white (females 59·2% and males 53·5%) and red (females 62·1% and males 51·7%) muscle. Lipid levels in the gonads increased gradually from the immature to spawning stage. The decrease of lipid in the somatic tissues was more intense in females than in males, and gonadal lipid content was higher in females than in males. There was a strong reverse correlation between water and lipid percentage in all tissues. Protein content decreased significantly only in spawning bonitos. The percentage of protein reduction from immature to spawning stage was relatively higher in males than in females in both white (females 3·4% and males 4·6%) and red (females 4·6% and males 5·1%) muscles. Protein content in the liver was significantly lower than in the other tissues, being highest in mature females. Gonadal protein content in females increased with maturation and decreased after spawning. The content in ash exhibited considerable stability. The RNA:DNA ratio exhibited a similar pattern of variation in both muscles. The RNA:DNA ratio increased during gonadal development gradually from the developing to spent stage. It was concluded that in S. sarda during gonadal development, there was an increase in gonadal lipid accompanied by a decrease in somatic tissue lipid reserves. Thus, reproductive inactive bonitos have more lipid in their edible part and a higher nutritional value than active ones.

Comparison of otolith growth and morphology with somatic growth and age in young‐of‐the‐year bluefin tuna - P. Megalofonou (Journal of Fish Biology, 2006)
Otolith morphological characteristics were studied using image analysis techniques and the relationships between otolith growth and somatic growth and age, as estimated from counting daily otolith increments, were examined in young‐of‐the‐year (YOY) bluefin tuna Thunnus thynnus ranging in fork length ( L F ) from 8·5 to 55·5 cm. Whole otolith length, width, area and perimeter, and three shape indexes, circularity, E value and rectangularity, were extracted for each pair of sagittae. Since no statistical significant differences between left and right otolith morphometrics were found, only one otolith from each fish was used for correlations. Statistically significant relationships were observed between otoliths measurements and fish somatic growth when a linear regression was applied after logarithmic transformation of all variables tested. Among the variables, otolith length was the one that showed the highest correlation with L F , followed by otolith area and perimeter, whereas otolith rectangularity exhibited the lowest correlation. Statistically significant relationships were also observed between the otolith variables tested and the age of the fish, which ranged from 20 to 129 days. The ages estimated using otolith mass were very close to those assessed using daily increment counts (bias ranged from 1 to 24 days). Therefore, otolith mass could represent a valuable criterion for age estimation in YOY bluefin tuna that is objective, economic and easy to perform compared to daily increment counting method.

Histological investigation on the ovarian cycle of the bluefin tuna in the western and central Mediterranean - A. Corriero; S. Desantis; M. Deflorio; F. Acone; C. R. Bridges; J. M. De la Serna; P. Megalofonou; G. De Metrio (Journal of Fish Biology, 2003)
The histological analysis of eastern Atlantic bluefin tuna Thunnus thynnus ovaries caught from February to September 1999–2000, made it possible to distinguish the presence of seven oocyte developmental stages and allowed the characterization of six time‐dependent ovary maturity stages. The ovaries of mature (fork length, L F ≥ 110 cm) bluefin tuna were non‐active from August (spent period) to March (quiescent period) when they contained only perinucleolar‐stage oocytes. Ovary development started in April to early May (recrudescent period) with the appearance of oocytes at the lipid stage. Vitellogenesis appeared in mid‐May (ripening period) and post‐vitellogenesis occurred in late May to mid‐June (pre‐spawning period). In late June to early July, hydrated oocytes, a sign of imminent spawning, were found only in specimens caught in Balearic waters. Females ranging between 100 and 110 cm L F , captured during the recrudescent and ripening periods, had the largest oocytes at the lipid stage, most of which were degenerating. An extensive vitellogenic atresia was observed in the ovaries of five females caught during the spawning period in non‐spawning areas.

Age and growth of Mediterranean albacore - P. Megalofonou (Journal of Fish Biology, 2000)
Estimated ages of 1136 individual albacore Thunnus alalunga (57–92 cm L F) from the Aegean and Ionian Sea ranged from 1 + to 9 years. Males grew faster and reached a greater size and age than females. No significant differences were found in the mean lengths at estimated ages between the two sampling areas. The von Bertalanffy growth model was fitted to mean lengths of estimated ages of individual fish and estimated growth parameters for the combined sexes were: L ∞ =94·7 cm, K =0·258, to=–1·354 years. Significant differences were found when the Mediterranean albacore growth parameters were compared with those determined for Atlantic Ocean albacore. It is not possible to determine if the differences in growth rates for the two populations are phenotypic or genotypic at the present time.